Water, sanitation, and hygiene service inequalities and their associated factors among urban slums and rural communities in Eastern Ethiopia - Mekonnen, Getachew Kabew; Zako, Abdurauf; Weldegebreal, Fitsum; Desalew, Assefa; Raru, Temam Beshir; Umer, Ukash; Urgesa, Kedir (Frontiers in Public Health, 2024)
Background: Understanding the level of inadequate water, sanitation and hygiene services in urban as well as rural settlements is crucial to prioritizing community interventions and resource allocation. However, there is a lack of evidence on discrepancies in water, sanitation and hygiene services across rural and urban slum communities in Ethiopia.The objective of this study is to assess households' water, sanitation and hygiene service inequalities and their associated factors among urban slum and rural communities, Eastern Ethiopia from February to Apriaccessl, 2024.Methods: A comparative community-based cross sectional study design was conducted, and study participants were selected by stratified random sampling with proportional-to-size allocation. Data were entered with Epi Data version 3.1 and then exported to STATA Version 17 for analysis. Bi-variable and multivariable logistic regression was employed, and associations were reported as an odds ratio with its 95% confidence intervals (CI) with a p-value less than 0.05 cut point.Result: A total of 278 urban and 301 rural households participated in the study, and the response rate was 94 %. Key indicators showed that WaSH services are significantly higher in urban than rural households: Improved water source in urban 98 % (95 % CI: 96, 99) compared to rural households, 76 % (95 % CI: 71, 80). Improved latrine was 44 % (95 % CI: 38, 50) in urban households and 14 % (95 % CI: 11, 19) in rural area. The proportion of hand washing practices at all five critical times among urban house heads was 52 % (95 % CI: 46, 58) and it was 22 % (95 % CI: 18, 27) among the rural households. Furthermore, type of occupation such as farmers (P = 0.000) and water service satisfaction (P = 0.000) are the common associated factors of the above three key WaSH outcomes.The study revealed that the WaSH services in urban slums were considerably higher than those in rural households. Socio-economic factors significantly influencing the existing WaSH services emphasize the stakeholders should provide strategic support to the community in order to alleviate the scarce WaSH service challenge.